Extensão rural pública em Angola: do modelo colonial à implementação das escolas de campo para agricultores - Mendes, Sebastião Jorge Agostinho (2022)
The general objective of this dissertation is to discover how Farmer Field Schools are implemented in the central and northern regions of Angola, as well as to reveal extensionists' perception of this approach regarding its advantages and limitations. As specific objectives, we sought to describe the origin, definition and foundations of Rural Extension; to identify the different transformations in public rural extension services throughout Angola's history and their relation to the political and social context; to analyze the implementation of Field Schools in the context of the MOSAP II project - Angola: its potentials and limits from point of view the rural extensionists working within the project. The construction and conduction of this study involved these three methodological processes: bibliographic research, carried out in books, periodicals and documents available on the internet; survey and semi-structured questionnaire submitted to the extension agents in Angola. The findings allowed us to identify that the introduction of Rural Extension services occurred in Angola in the 1960s and 1970s through a cooperation between the Brazilian government, the Portuguese government and the Department of African Studies of the Institute for Economic Research of Munich (IFFO). The first services were adapted from the now defunct Associação de Crédito e Assistência Rural do Estado de Santa Catarina (ACARESC) in the state of Santa Catarina (Brazil). ACARESC used a methodological approach based on diffusionism. With the criticism to this intervention model, Angola tried to adopt approaches based on the participation of the different local agents in the intervention processes in the rural environment, with the introduction of Farmer Field Schools, from 2005 on, as the main approach of extensionist action. The first moment of the field research sought to identify the extensionists' profile. The second moment allowed to understand how extensionist action occurs in practice, through their work in the Field Schools conducted by the MOSAP project in these three provinces of Angola - Malanje, Huambo and Bié. We conclude that although the Field School approach is promising for the Angolan context, it has some limitations linked to the political, economic, social, cultural and historical conditions of Angola.